Preferences for Redistribution and International Migration - Ilpo Kauppinen; Panu Poutvaara (ZBW - Leibniz Information Centre for Economics, 2020)
Are migrants self-selected and sorted according to their views about what constitutes a fair level of redistribution? A major challenge in answering this question is that fairness concerns and self-interest are intertwined. We present a theoretical framework that allows us to test whether migrants self-select and sort themselves according to fairness concerns, in addition to financial self-interest. Our empirical analysis uses our own survey data on Danish emigrants to various destinations, combined with full-population administrative data and survey data on Danes living in Denmark. To exclude the role of financial self-interest, we focus on emigrants' attitudes towards redistribution in Denmark where they no longer pay taxes or receive transfers. We find strong support for the hypothesis that migrants self-select and sort themselves according to their views about what constitutes a fair level of redistribution among men, but not among women: the majority of men who emigrate are more negative towards redistribution in Denmark than non-migrants, while the opposite pattern prevails among women. The stark gender difference remains when solely looking at those who emigrated for work reasons.
Keywords: F22; 330; Migration; Emigration; Welfare state; Redistribution; Political preferences